3D VISUALIZATION AND MODELING OF HUMAN ORGANS USING INNOVATIVE TECHNOLOGIES (International scientific-electronic journal “Pioneering studies and theories”, 2025)
The article analyzes the scientific–methodological foundations and modern technological approaches to three-dimensional (3D) visualization and modeling of human organs in the medical field. It explores the processes of processing DICOM-formatted CT/MRI data, performing segmentation, and creating 3D anatomical models using environments such as Blender, 3D Slicer, Unity, and Unreal Engine. The proposed methodology is aimed at improving medical diagnostics, surgical planning, and clinical analysis processes. Furthermore, the article substantiates the scientific and practical significance of developing a 3D anatomy system with an Uzbek-language interface based on local medical terminology.